Food safety performance tool - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Food safety performance tool applied to all of Africa. There's one for country level and value chain level (Vietnam, six different value chains). This is stage 1. It was published for the Bill and Melinda Gates Foundation, but planning to validate more.